2022
DOI: 10.3390/molecules27217356
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of the Essential Oils of Citral-Rich Chemotype Cinnamomum camphora and Cinnamomum bodinieri

Abstract: Citral chemotypes Cinnamomum camphora (C. camphora) and Cinnamomum bodinieri (C. bodinieri) are promising industrial plants that contain abundant citral. For a more in-depth study, their significant biological effect, the chemical composition and antioxidant capacity of essential oils of citral-rich chemotype C. camphora and C. bodinieri (EOCC) were determined in the present study. The EOCC yield, obtained by hydro-distillation and analyzed by gas chromatography–mass spectrometry (GC-MS), ranged from 1.45–2.64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…C. camphora can be categorized into different chemotypes depending on the main compound of its leaf essential oils, namely camphor‐type, linalool‐type, cineol‐type, isonerolidol‐type, and borneol‐type. Citral chemotypes of C. camphora representing neral, geranial, isocitral, geraniol, and caryophyllene as major compounds were also reported from China [33–34] . C. camphora essential oils isolated by supercritical carbon dioxide extraction, hydrodistillation, ethanol extraction, and petroleum ether extraction were also found richly composed of sesquiterpenes (α‐phellandrene, α‐terpinene) and oxygenated monoterpenes (β‐terpineol, eucalyptol) [35] .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…C. camphora can be categorized into different chemotypes depending on the main compound of its leaf essential oils, namely camphor‐type, linalool‐type, cineol‐type, isonerolidol‐type, and borneol‐type. Citral chemotypes of C. camphora representing neral, geranial, isocitral, geraniol, and caryophyllene as major compounds were also reported from China [33–34] . C. camphora essential oils isolated by supercritical carbon dioxide extraction, hydrodistillation, ethanol extraction, and petroleum ether extraction were also found richly composed of sesquiterpenes (α‐phellandrene, α‐terpinene) and oxygenated monoterpenes (β‐terpineol, eucalyptol) [35] .…”
Section: Resultsmentioning
confidence: 87%
“…Citral chemotypes of C. camphora representing neral, geranial, isocitral, geraniol, and caryophyllene as major compounds were also reported from China. [33][34] C. camphora essential oils isolated by supercritical carbon dioxide extraction, hydrodistillation, ethanol extraction, and petroleum ether extraction were also found richly composed of sesquiterpenes (α-phellandrene, α-terpinene) and oxygenated monoterpenes (β-terpineol, eucalyptol). [35] In a previous study by Ahmed et al [36] (E)-caryophyllene (25.3 %), linalool (13.4 %), and caryophyllene oxide (10.3 %) were reported as the main components in C. tamala leaves oil.…”
Section: Chemical Composition Of Cinnamomum Speciesmentioning
confidence: 99%
“…Additionally, carvone has been considered as a protective molecule against lipid peroxidation 12 . Furthermore, the monoterpenes citral, a major component identified in C. flexuosus EO, has also shown promising antioxidant properties 53 , 54 . Similar to monoterpenes, sesquiterpenes can act as direct antioxidants, neutralizing free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…EO ( F ) is rich in oxygenated monoterpenes; these types of compounds possess various biological properties, including antioxidant ones [ 87 ]. Other studies on the antioxidant activity of EO have shown that the abatement ability of ABTS radicals is closely related to the concentration of EOs and has a strong connection with its chemical components, especially its main constituents [ 88 ].…”
Section: Resultsmentioning
confidence: 99%